Large-Scale Genomic Analyses and Toxinotyping of Clostridium perfringens Implicated in Foodborne Outbreaks in France - Mahamat Abdelrahim, Abakabir; Radomski, Nicolas; Delannoy, Sabine; Djellal, Sofia; Le Négrate, Marylène; Hadjab, Katia; Fach, Patrick; Hennekinne, Jacques-Antoine; Mistou, Michel-Yves; Firmesse, Olivier (Frontiers in Microbiology, 2019)
Clostridium perfringens is both an ubiquitous environmental bacterium and the fourth most common causative agent of foodborne outbreaks (FBOs) in France and Europe. These outbreaks are known to be caused by C. perfringens enterotoxin (CPE) encoded by the cpe gene. However, additional information on the toxin/virulence gene content of C. perfringens has become available in the last few years. Therefore, to understand the enteropathogenicity of this bacterium, in the context of foodborne outbreaks, we need to describe the toxin and virulence genes content diversity of the implicated strains regardinginvolved in foodborne outbreaks, toxin and virulence genes. In this study, we used a new real-time PCR typing technique based on a comprehensive set of 17 genes encoding virulence factors. The analysis was performed on a collection of 141 strains involved in 42 foodborne outbreaks in the Paris region. It was combined with whole genome sequence (WGS) phylogenomic reconstruction, based on the coregenome single nucleotide polymorphisms (SNPs) of 58 isolates, representatives of the identified virulence gene profiles. Two or threeUp to three different virulence gene profiles were detected in 10 FBOs, demonstrating that C. perfringens foodborne outbreaks may be associated with heterogeneous strains. cpe-positive strains were isolated in 239 outbreaks, confirming the prominent role of CPE in pathogenicity. However, while C. perfringens was the sole pathogen isolated from the incriminated food, the cpe gene was not detected in strains potentially related to 132 outbreaks. This result indicates either that the standard method was not able to isolate cpe+ strains or that the cpe gene may not be the only determinant of the enterotoxigenic potential of C. perfringens strains. Using phylogenomic reconstruction, we identified two clades distinguishing chromosomal cpe-positive from cpe-negative and plasmid-borne cpe. Important epidemiological information was also garnered from this phylogenomic reconstruction that revealed unexpected links between different outbreaks associated with closely related strains (7 SNP differences) and having common virulence gene profiles. This study provides new insight into the characterization of foodborne C. perfringens and highlights the potential of WGS for the investigation of FBOs.